Influence of serotonin on the analgesic effect of granisetron on temporomandibular joint arthritis. Issue 5 (2004) - Voog, Ülle; Alstergren, Per; Leibur, Edvitar; Kallikorm, Riina; Kopp, Sigvard
Abstract : THE influence of circulating serotonin (5-HT) on the effects of intra-articular administration of granisetron on temporomandibular joint (TMJ) pain was investigated in 11 patients with chronic polyarthritides. An analgesic effect superior to placebo has been shown previously. The change in TMJ movement pain intensity was negatively correlated to circulating 5-HT; that is, the higher the 5-HT before injection, the greater the reduction of pain intensity. The resting pain intensity reduction was not related to 5-HT. In conclusion, this study indicates a stronger short-term analgesic effect on TMJ movement pain by intra-articular administration of the 5-HT3 receptor antagonist granisetron in patients with high levels of circulating 5-HT.